Catching-up regional strategy as a tool to reduce spatial inequality; Journal of the Geographical Institute Jovan Cvijic SASA; Vol. 73, No. 1 - Chistyakova N. O. Natalya Olegovna; Mikhalchuk A. A. Aleksandr Alexandrovich; Bocharova Yu. S Yuliya Sergeevna; Akerman E. A. Ekaterina Aleksandrovna; Tatarnikova V. V. Valeriya Vladimirovna (2023, 2023)
Title screen